An investigation of speaking anxiety among Saudi English language learners - Altamni, Thuraya (2015)
Abstract English is considered as the international language in a number of fields, such as science, medicine, business, commerce and diplomacy. This may increase the demand to learn spoken English in order to communicate with people with different languages from different parts of the world. Unfortunately, learning this skill might be negatively affected by such factors as anxiety, which is the main concern of the present project. The reason for the concentration on this factor is to investigate whether Saudi students in both general and pre-sessional English courses in the UK are anxious about speaking in language classes, in addition to exploring the core causes of their apprehension about speaking English in class. The findings indicate that speaking anxiety is associated with the majority of Saudi pupils on these two types of courses. Although it was hypothesized that the main reason for their anxiety was their low level of English, the results revealed that the major cause was their worry about making mistakes when speaking in class. The other reasons for their anxiety were related to their low competence in English, competitiveness and comparisons between language learners, personality traits such as feeling self-conscious when speaking English, and teachers’ and students’ behaviours and reactions, especially when a language instructor calls on a student to speak or respond in the classroom.